PENDIDIKAN PEMAKAI DALAM PEMANFAATAN FASILITAS DAN LAYANAN DI UPT PERPUSTAKAAN STMIK STIKOM INDONESIA - Nugraha, Hajus Satria; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2018)
ABSTRACT User education is an activity that has an important influence on the optimal utilization of aservice and activities in the library. This study aims to determine the conditions of user education implementation and the influence of user education on the utilization of facilities and service at UPT STMIK STIKOM Indonesia Library. This library has some facilities and adequate services supported by user education programs to provide education about the library to the entire academic community STMIK STIKOM Indonesia with the aim to utilize the facilities and services available effectively and efficiently. This study discusses the effect of user education on facilities and services with quantitative and descriptive methods. Sources of data in this study comes from primary data through observation and questionnaires, and secondary data such as the history of STMIK STIKOM Indonesia Library, employee data, organizational structure, visit statistics and mission vision. Other sources of data come from articles in journals, textbooks, website sites, previous research and direct observation. Data analysis techniques in this study using the validity test, reliablitas test, and simple regression analysis using SPSS software (Statistical Package Social Science). The result shows that there is a significant influence between user education on the utilization of facilities and services at UPT STMIK STIKOM Indonesia Library. Keywords: User Education, Library Serviceand Facilities